Process development for the production of protein hydrolysate from cockle (Anadara granosa) meat wash water - Haslaniza, H.; Maskat, M.Y.; Wan Aida, W.M.; Mamot, S. (Universiti Kebangsaan Malaysia, 2014)
A study was carried out to determine the process parameters and optimization for the hydrolysis of protein precipitate from cockle (Anadara granosa) meat wash water. Precipitation of the protein in the wash water was done using pH manipulation (pH3-8). The precipitate was hydrolyzed using hydrochloric acid (HCl) and optimized for HCl volume, HCl concentration and hydrolysis time using response surface methodology (RSM) based on a central composite rotatable design. Based on the results, hydrolysis of cockle meat wash water precipitate was carried out by precipitation of the wash water at pH4. Optimum condition for the hydrolysis of 2.0 g of cockle meat wash water precipitate was 25 mL of 1 N HCl for 10 h which resulted in nitrogen content (NC) of 0.7% and degree of hydrolysis (DH) of 55%. NC and DH were significantly influenced only by the hydrolysis time.